Kazakhstan : Overview of Tobacco Use, Tobacco Control Legislation, and Taxation - World Bank Group (World Bank, Washington, DC, 2019)
The country brief provides an overview of tobacco legislation, use, and taxation in Kazakhstan. Tobacco taxation policy practiced in Kazakhstan in 2003-2013 resulted in increased tobacco excise revenues, but was not effective in terms of public health, as cigarette consumption did not decrease. Tobacco excise taxes were drastically increased in Kazakhstan from 1 January 2014; and thereafter, the tobacco affordability was substantially reduced resulting in the subsequent decline in tobacco sales and smoking prevalence in the country. Decline in consumption could have an effect on tobacco-related mortality in Kazakhstan. Mortality rates of some tobacco-related causes of death substantially declined in Kazakhstan in 2013–2015 among men and women aged 30 to 79 years: by about 20 percent for acute ischemic heart disease and stroke and by 30–40 percent for respiratory tuberculosis and chronic obstructive pulmonary disease. Kazakhstan returned to a policy of moderate tax increases in 2015-2019. The reduction in tobacco affordability in 2015 was caused not only by the excise increase but also by the tobacco industry pricing policy and a decline in real incomes. Tobacco consumption in Kazakhstan decreased in 2015, but the revenue increase was smaller than expected. A moderate excise rise in 2016- 2018 could not ensure a substantial reduction in tobacco affordability, and annual tobacco sales did not change much. The country experience shows that a policy of moderate (below 30 percent annually) excise increases cannot ensure either tobacco consumption reductions or substantial revenue increases. The planned annual cigarette excise increase for 2020–2021, however, is only 12–14 percent. In recent years, electronic cigarettes and heated tobacco appeared in the Kazakhstan market. The key consumers of such products are young adults, who follow modern trends, rather than dependent smokers looking for an effective means to quit. Heated tobacco products and liquids for electronic cigarettes will be taxed by excise from 2020, but the excise rates are very low and should be substantially increased. Kazakhstan has great potential to increase its excise rates for all kinds of tobacco products to contribute to health objectives by means of reducing tobacco consumption. The greater the excise tax increase, the larger the reduction in tobacco consumption and the higher tobacco excise revenue growth will be.